2012 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP) 2012
DOI: 10.1109/icassp.2012.6288834
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the memory of BLSTM Neural Networks for enhanced emotion classification in dyadic spoken interactions

Abstract: Recent studies indicate that bidirectional Long Short-Term Memory (BLSTM) recurrent neural networks are well-suited for automatic emotion recognition systems and may lead to better results than systems applying other widely used classifiers such as Support Vector Machines or feedforward Neural Networks. The good performance of BLSTM emotion recognition systems could be attributed to their ability to model and exploit contextual information self-learned via recurrently connected memory blocks which allows them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…Then, newly reconstructed data are obtained by applying this rule on the emotion-specific data in a different domain. Wollmer et al [41] presents a method to systematically investigate the number of past and future utterance-level observations that are considered to generate an emotion prediction for a given utterance, and to examine to what extent this temporal bidirectional context contributes to the overall performance.…”
Section: B Feature Extractionmentioning
confidence: 99%
“…Then, newly reconstructed data are obtained by applying this rule on the emotion-specific data in a different domain. Wollmer et al [41] presents a method to systematically investigate the number of past and future utterance-level observations that are considered to generate an emotion prediction for a given utterance, and to examine to what extent this temporal bidirectional context contributes to the overall performance.…”
Section: B Feature Extractionmentioning
confidence: 99%
“…In previous work on the IEMOCAP database, LLD features are also widely used for acoustic models (e.g., [33][34][35]). However, recent work has shown that knowledge-inspired global prosodic features are more predictive than the LLD features for predicting binary Arousal values [36].…”
Section: Related Workmentioning
confidence: 99%
“…The LSTM-RNN model was used directly for classification in previous work on the IEMOCAP database. Results have shown that LSTM-RNN models have better performance than Hidden Markov Models (e.g., [33,34]). Another application of deep learning methods uses Denoising Autoencoders to model gender information, which is shown to help with the emotion recognition task [37].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…2) Features: Previous work on both the AVEC2012 and the IEMOCAP databases have focused on LLD features for the acoustic model (e.g., [25], [26]). However, there are results indicating that knowledge-inspired features, such as global prosodic features, may also be more predictive (e.g., [27], [28]).…”
Section: ) Databasesmentioning
confidence: 99%